Relationship between internalized stigma and treatment efficacy in mixed neurotic spectrum and depressive disorders - Ociskova, Marie; Prasko, Jan; Kamaradova, Dana; Grambal, Ales; Latalova, Klara; Sigmundova, Zuzana (Neuro endocrinology letters, 2014)
OBJECTIVE: Many psychiatric patients suffer from self-stigma. One consequence of these internalized prejudices is decreased treatment efficacy. Much has been written about the effects of self-stigma in patients with severe mental disorders. However, individuals with minor psychiatric disorders also suffer from self-stigma. It is therefore necessary to explore the effect of self-stigma on treatment efficacy of neurotic patients. METHOD: Aim of out study was to investigate relationship between self-stigma, severity of symptoms, and presence of comorbidit disorder and treatment outcome in neurotic patients. Patients were treated by combined psycho and pharmacotherapy. Level of self-stigma was measured by Internalized Stigma Of Mental Illness scale. Severity of anxiety and depressive symptoms was assed by Beck Anxiety Inventory, Beck Depressive Inventory and Clinical Global Impression Scale. RESULTS: Level of self-stigma was significantly correlated with the levels of anxiety, depression and global evalutions of a mental state on the beginnig of the therapy. Up to our results patients with higher level of self-stigmatization had lower improvement after combined treatmet in respect to perceived anxiety symptoms. CONCLUSION: Self-stigma seems to be an important factor influencing efficacy of combined treatment. More researches focused on self-stigmatization should be done to find an optimal therapeutic strategy for patients with higher level of self-stigmatization.
Keywords: kombinovaná terapie; depresivní poruchy; lidé; Depressive Disorder; výsledek terapie; Adult; Combined Modality Therapy; Middle Aged; Antidepressive Agents; Neuroticism; Female; Psychotherapy; Humans; Self Concept; neuroticismus; Anxiety Disorders; psychoterapie; lidé středního věku; úzkostné poruchy; antidepresiva; mužské pohlaví; sebepojetí; ženské pohlaví; Treatment Outcome; Male; společenské stigma; Social Stigma; dospělí